Long term results after surgical basal cell carcinoma excision in the eyelid region. Issue 1 (1st January 1999) - Pieh, Stefan; Kuchar, Andreas; Novak, Philipp; Kunstfeld, Rainer; Nagel, Gunda; Steinkogler, F J
Abstract : AIMS: To evaluate the data for patients with basal cell carcinoma (BCC) in the eyelid region, to demonstrate histologically controlled tumour excision, and to prove the efficacy of the treatment on the basis of long term observations. METHODS: Retrospective analysis of 382 microscopically controlled BCC excisions in the eyelid apparatus (350 patients) in a follow up study over 5.7 (SD 1.1) years. Tumour location, tumour size, and histological results were recorded. The same procedure was followed for recurrences. Follow up examinations were carried out 1, 3, 6, and 12 months after the operation, and then annually for a further 4 years or longer. RESULTS: A recurrence rate of 5.36% was observed after the primary operation. 60.3% of first recurrences occurred in the medial canthus, 41.2% showed in depth extension, and sclerosing types were overly represented at 35.3%. After the second operation the recurrence rate increased to 14.7% and reached 50% after a third and fourth operation. CONCLUSIONS: The greatest risk of recurrence exists for BCCs of the medial canthus with in depth extension, and for sclerosing types. The recurrence rate increases after every operation. For high risk cases, consideration should be given to adjuvant treatment such as radiotherapy.